1996
DOI: 10.1161/01.res.79.5.984
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Endothelial Nitric Oxide Synthase in Response to Fluid Shear Stress

Abstract: Endothelial cells release nitric oxide (NO) more potently in response to increased shear stress than to agonists which elevate intracellular free calcium concentration ([Ca2+]i). To determine mechanistic differences in the regulation of endothelial constitutive NO synthase (ecNOS), we measured NO production by bovine aortic endothelial cells exposed to shear stress in a laminar flow chamber or treated with Ca2+ ionophores in static culture. The kinetics of cumulative NO production varied strikingly: shear stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
302
0
12

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 452 publications
(326 citation statements)
references
References 27 publications
11
302
0
12
Order By: Relevance
“…Shear stress has also been shown to increase pro-oxidants, including NOS formation of NO and SOD (Malek et al 1995;Uematsu et al 1995;Corson et al 1996;Dimmeler et al 1999;Woodman et al 1999 under H 2 O 2 -induced oxidative stress under both shear and static conditions. The overall goal of these studies is to provide a possible model for disease development within the vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Shear stress has also been shown to increase pro-oxidants, including NOS formation of NO and SOD (Malek et al 1995;Uematsu et al 1995;Corson et al 1996;Dimmeler et al 1999;Woodman et al 1999 under H 2 O 2 -induced oxidative stress under both shear and static conditions. The overall goal of these studies is to provide a possible model for disease development within the vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in Ca 2+ signalling have been described in diabetes [36,37], although this is unlikely to affect βAR-mediated NOS3 activation, as this activation has been shown to occur without detectable changes in intracellular Ca 2+ either in human vascular endothelial cells [38] or in platelets [6]. It has been reported that sheer stress can activate NOS3 in a Ca 2+ -independent manner [39]. This is due to phosphorylation of the NOS3 serine residue Ser 1177 , which alters the enzyme's sensitivity to Ca 2+ , enabling maximal activity at sub-physiological concentrations of Ca 2+ [40].…”
Section: Discussionmentioning
confidence: 99%
“…These include protein-protein interactions [22][23][24][25][26], protein phosphorylation [27][28][29], endogenous inhibitory N-methylated L-arginines [30,31], subcellular localization [32], subunit dimerization [33], as well as product feedback inhibition, by which excess NO down-regulates the amount of subsequent NO synthesis. NOS activity can also be altered by oxidative stress.…”
Section: Introductionmentioning
confidence: 99%